(3efGbH (B((3CejQ GdeDefjf(B) (3YeQ Hf GdNWGH QVj Gddg Yfgs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3Ydj Hf eMeO Hf YKeGf Hf YHOGdUeO GdOfOjdj GdTGaYj s)
(3ChdgG (B:s
(3aj GdZjQI abdJ dgf(B: (3YSi Cf Wdbcf Cf jHO dg CRhGLG NjQkG efcf afRdJ cPdc s
(3BNQgG (B:s
(3QCjJ GdfHj Udi Gddg Ydjg hSde ai efGej abGd di(B: (3gGgfG bhe jTJehf CHG HcQ hYeQ, hgeGefi HefRdI gGJjf hbQf Hjf CUHYjf(B: (3GdSHGHI hGdhSWi, aef TJegeG abO TJefi BNQ GdcJGH hGdMeO ddg hMOg s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B423 ; (3eDdaGJ Hf GdLhRj (B- (3U (B180 s
Keywords: (3GdJGQjNs